Appraisal of crop production in agri-horti-silvicultural system under aridirrigated conditions of Punjab - BRAR, J S; GUPTA, NAVJOT; KAUR, KIRANDEEP; KAUR, GAGANDEEP; MANHAS, S S (The Indian Journal of Agricultural Sciences, 2020)
In agri-horti-silvicultural model, the growth, yield and economic appraisal of intercropping of moong-chickpea rotation and turmeric was studied during 2014-18 under arid-irrigated conditions of Punjab. The model comprising one silvicultural crop (poplar), fruit crops (peach, plum, guava and citrus) and agronomic crops (moong-chickpea rotation and turmeric) were evaluated in different combinations. The moong- chickpea rotation and turmeric were also cultivated as sole crops for comparative analysis. The results revealed that the yield of all agronomic crops was the maximum under sole cropping leading to B:C ratio of 2.30 and 2.39 in moong-chickpea rotation and turmeric respectively followed by intercropping in poplar. Among different agri-silvi-horti combinations, the B:C ratio in system including deciduous fruit plants such as peach and plum was better as compared to evergreen fruit plants of guava and citrus. Cultivation of turmeric under different combinations was more beneficial than moong-chickpea crop rotation. Thus, it was concluded that during pre-bearing phase of fruit plants and before economic growth of poplar, the cultivation of turmeric is more profitable in agri-horti-silvicultural model. This model has potential for higher productivity of different crops in addition to natural resource conservation, efficient use of land and other resources.